Pedicle screw placement with use of a navigated surgical drill at subaxial cervical spine. (June 2021) - Satake, Kotaro; Kanemura, Tokumi; Ito, Kenyu; Tanaka, Satoshi; Morita, Yoshinori; Nakashima, Hiroaki; Ouchida, Jun; Imagama, Shiro
Highlights: Navigated drill reduces the lateral/rostral deviation of cervical pedicle screw. The drill set in low speed can graze the cortex of cervical pedicle safely. The drill is useful to reduce the injuries of vertebral artery and nerve roots. Abstract: Study design: Retrospective cohort study. Objective: This study was performed to evaluate the accuracy of cervical pedicle screw (CPS) placement with use of a navigated surgical drill (ND) and to compare it with navigated manual probe (MP) at C3–C6. Methods: 47 consecutive patients (27 males and 20 females, 67.2 [33–91] years) underwent a posterior cervical fixation using CPSs under an intraoperative 3D - – CT based navigation system (total 207 CPSs). For initial probing, ND with 2.2-mm steel burr was used since Apr. 2017 (Group ND; 33 patients, 152 CPSs). MP was used earlier (Group MP; 14 patients, 55 CPSs). There were no other different procedures between the two groups. The accuracy of CPS placement was graded with postoperative CT and compared between the two groups. Results: There were no significant differences in the total perforation rates both in axial and sagittal planes between Groups ND and MP (axial; 7.2% vs. 14.5%, p = 0.25, sagittal; 10.5% vs. 14.5%, p = 0.46). However, the lateral and rostral perforation rates were significantly reduced in Group ND compared to Group MP (lateral: 36.4% vs. 87.5%, p = 0.04; rostral: 6.3% vs. 100%, p = 0.001). Conclusion: Although ND did not decrease the total perforation rate significantly, it reduced the incidence of lateral and rostral perforation. ND is likely to make initial probing easier without a forcible manipulation which might cause vertebral rotation.